Surgical Complications after Targeted Muscle Reinnervation at a Safety-Net Hospital - Obinero, Chioma G.; Green, Jackson C.; Swiekatowski, Kylie R.; Obinero, Chimdindu V.; Manisundaram, Arvind; Greives, Matthew R.; Bhadkamkar, Mohin; Wu-Fienberg, Yuewei; Marques, Erik (Journal of Reconstructive Microsurgery, 2024)
Background Targeted muscle reinnervation (TMR) and regenerative peripheral nerve interface (RPNI) can reduce neuroma formation and phantom limb pain (PLP) after lower extremity (LE) amputation. These techniques have not been studied in safety-net hospitals. This study aims to examine the surgical complication rates after TMR and/or RPNI at an academic safety-net hospital in an urban setting.Methods This was a retrospective review of patients older than 18 years who had prior above-knee guillotine amputation (AKA) or below-knee guillotine amputation (BKA) and underwent stump formalization with TMR and/or RPNI from 2020 to 2022. Demographics, medical history, and operative and postoperative characteristics were collected. The primary outcome was any surgical complication, defined as infection, dehiscence, hematoma, neuroma, or reoperation. Univariate analysis was conducted to identify variables associated with surgical complications and PLP.Results Thirty-two patients met the inclusion criteria. The median age was 52 years, and 75% were males. Indications for amputation included diabetic foot infection (71.9%), necrotizing soft tissue infection (25.0%), and malignancy (3.1%). BKA was the most common indication for formalization (93.8%). Most patients (56.3%) had formalization with TMR and RPNI, 34.4% patients had TMR only, and 9.4% had RPNI alone. The incidence of postoperative complications was 46.9%, with infection being the most common (31.3%). The median follow-up time was 107.5 days. There was no significant difference in demographics, medical history, or operative characteristics between patients who did and did not have surgical complications. However, there was a trend toward higher rates of PLP in patients who had a postoperative wound infection (p = 0.06).Conclusion Overall complication rates after LE formalization with TMR and/or RPNI at our academic safety-net hospital were consistent with reported literature. Given the benefits, including reduced chronic pain and lower health care costs, we advocate for the wider adoption of these techniques at other safety-net hospitals.
Keywords: targeted muscle reinnervation; regenerative peripheral nerve interface; nerve transfer; safety-net hospital; surgical complications; lower extremity; amputation